Approximating endpoints of multi-valued nonexpansive mappings in Banach spaces - Bancha Panyanak (2018)
© 2018, Springer International Publishing AG, part of Springer Nature. The purpose of this paper is to introduce a modified Ishikawa iteration for multi-valued mappings and show that the proposed iteration pattern will converge to an endpoint of a certain multi-valued nonexpansive mapping.